2006
DOI: 10.1111/j.1540-8167.2005.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Diffusion‐Weighted Magnetic Resonance Imaging: A Tool to Monitor the Thrombogenicity of Left Atrial Catheter Ablation

Abstract: This is the first study using highly sensitive DW-MRI of the brain to detect asymptomatic cerebral embolism after left atrial catheter ablation. Even small, clinically silent, embolic lesions can be demonstrated with this technique. DW-MRI can be used to monitor and compare the thrombogenicity of different AF ablation approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
86
4
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(96 citation statements)
references
References 41 publications
4
86
4
2
Order By: Relevance
“…1 This procedure, however, requires great attention to prevent both thromboembolic and hemorrhagic complications such as cerebral infarctions and cardiac tamponade. [1][2][3] Several studies have shown that the periprocedural continuation of therapeutic warfarin could reduce thromboembolic complications without increasing the risk of hemorrhagic complications. [4][5][6][7][8][9] In addition, it has been reported that cardiac tamponade as a complication of AF ablation is not difficult to manage when the procedure is performed under therapeutic international normalized ratio (INR).…”
mentioning
confidence: 99%
“…1 This procedure, however, requires great attention to prevent both thromboembolic and hemorrhagic complications such as cerebral infarctions and cardiac tamponade. [1][2][3] Several studies have shown that the periprocedural continuation of therapeutic warfarin could reduce thromboembolic complications without increasing the risk of hemorrhagic complications. [4][5][6][7][8][9] In addition, it has been reported that cardiac tamponade as a complication of AF ablation is not difficult to manage when the procedure is performed under therapeutic international normalized ratio (INR).…”
mentioning
confidence: 99%
“…7,8 In contrast to clinically evident stroke, few data exist on the possibility of experiencing a silent cerebral embolism in the context of AF ablation. 9,10 Because of these considerations, knowledge of the incidence of silent cerebral embolism as well as clinically manifest stroke in the context of AF ablation is important. These data will enable us to fully comprehend the clinical implications of AF ablation and to better assess the risk profile of the procedure.…”
mentioning
confidence: 99%
“…1 Recent data suggest, that clinically apparent cerebral ischemia is only the "tip of the iceberg" because silent ischemic lesions can be demonstrated by diffusionweighted cerebral MRI in a much higher proportion of the patients undergoing left atrial (LA) ablation. [2][3][4][5][6][7] Although the clinical relevance of these lesions is unknown, they raise new concerns regarding the safety of AF ablation. Importantly, a significant correlation has been demonstrated between the incidence of these cerebral lesions and the ablation technology used: circular multipolar phased radiofrequency (RF) ablation has consistently been associated with the highest incidence of new lesion formation, in up to 37% of the procedures, whereas cryoenergy seems to be the safest technique.…”
mentioning
confidence: 99%